2018
DOI: 10.18683/germs.2018.1135
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant bacteria isolated from cell phones in five intensive care units: Exploratory dispersion analysis

Abstract: Cell phones are contaminated with highly harmful bacteria and potentially can maintain them for prolonged periods of time. These devices could be considered as a potential source of nosocomial infections in ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
8
0
5
Order By: Relevance
“…The authors reported that smartphones were more often contaminated by pathogenic bacteria than mobile phones (35% vs. 20%) because of larger surfaces and additional features. Although our initial hypothesis was along the same line, we did not observe a higher level of contamination in smartphones than mobile In our study, none of the pathogenic bacteria showed antimicrobial resistance while VRE, MRSA, and imipenem resistant Acinetobacter strains were identified by Loyala S. et al (16). One of our initial goals was to investigate crosscontamination between the cellular phone and the patient.…”
Section: Discussionmentioning
confidence: 49%
“…The authors reported that smartphones were more often contaminated by pathogenic bacteria than mobile phones (35% vs. 20%) because of larger surfaces and additional features. Although our initial hypothesis was along the same line, we did not observe a higher level of contamination in smartphones than mobile In our study, none of the pathogenic bacteria showed antimicrobial resistance while VRE, MRSA, and imipenem resistant Acinetobacter strains were identified by Loyala S. et al (16). One of our initial goals was to investigate crosscontamination between the cellular phone and the patient.…”
Section: Discussionmentioning
confidence: 49%
“…In recent years, the use of mobile devices has increased, and this carries a subsequent risk that they too may be colonized by multidrug-resistant microorganisms from the clinical setting. Several gram-positive pathogenic bacteria, such as S. aureus and Enterococcus species, as well as gramnegative bacteria like Acinetobacter species, E. coli, K. pneumoniae, and Pseudomonas species that are known to be significant causes of nosocomial infection have been isolated from mobile phones, while the rate of multidrug resistance in gram-negative bacteriaespecially Pseudomonas species, K. pneumoniae, and Citrobacter species -isolated from mobile phones is reported to be 70% and the rate of MRSA isolation in another study was found to be 26% [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…La mediana de contaminación bacteriana reportada en el presente trabajo es similar a la encontrada por la mayoría de los estudios revisados 9,25,37,39,[26][27][28][29]31,32,35,36 . No obstante, el nivel de contaminación reportado fue distinto al identificado por una minoría de autores 6,21 .…”
Section: Discussionunclassified